The Fantastic Four behold ... Galactus! - Lee, Stan 1922-2018; Byrne, John 1950-; Kirby, Jack 1917-1994 (Marvel Worldwide, Inc., 2019)
"The Fantastic Four take on their biggest foe -- literally! First, Stan Lee and Jack Kirby introduce Galactus and his enigmatic herald, the Silver Surfer, as they come of Earth in one of the greatest comic-book sagas ever told! Next John Buscema's powerful pencils illustrate the arrival of new herald Gabriel the Air-Walker, signaling doom for the human race! Then, John Byrne takes over as Terrax leads the Devourer back to Earth -- and the entire Marvel Universe pitches in to help the FF save the planet from becoming his next meal!"--Back cover
Collecting Fantastic Four (1961) #48-50, #120-123, and #242-244 -- Back cover
Keywords: Superheldin; Superheld; Comic